Disruption of the immune-checkpoint VISTA gene imparts a proinflammatory phenotype with predisposition to the development of autoimmunity - Wang, Li; Le Mercier, Isabelle; Putra, Juan; Chen, Wenna; Liu, Jun; Schenk, Austin D; Nowak, Elizabeth C; Suriawinata, Arief A; Li, Jiannan; Noelle, Randolph J (Proceedings of the National Academy of Sciences - PNAS, 2014)
V domain-containing Ig suppressor of T-cell activation (VISTA) is a negative checkpoint regulator that suppresses T cell-mediated immune responses. Previous studies using a VISTA-neutralizing monoclonal antibody show that VISTA blockade enhances T-cell activation. The current study describes a comprehensive characterization of mice in which the gene for VISTA has been deleted. Despite the apparent normal hematopoietic development in young mice, VISTA genetic deficiency leads to a gradual accumulation of spontaneously activated T cells, accompanied by the production of a spectrum of inflammatory cytokines and chemokines. Enhanced T-cell responsiveness was also observed upon immunization with neoantigen. Despite the presence of multiorgan chronic inflammation, aged VISTA-deficient mice did not develop systemic or organ-specific autoimmune disease. Interbreeding of the VISTA-deficient mice with 2D2 T-cell receptor transgenic mice, which are predisposed to the development of experimental autoimmune encephalomyelitis, drastically enhanced disease incidence and intensity. Disease development is correlated with the increase in the activation of encephalitogenic T cells in the periphery and enhanced infiltration into the CNS. Taken together, our data suggest that VISTA is a negative checkpoint regulator whose loss of function lowers the threshold for T-cell activation, allowing for an enhanced proinflammatory phenotype and an increase in the frequency and intensity of autoimmunity under susceptible conditions.